New York City 2026 - Keeling, Stephen (Travel writer) (Eyewitness travel guides., 2025)
"Whether you want to visit the iconic Empire State Building, take a leisurely stroll through Central Park, or sample the sublime cocktails in East Village, your DK Eyewitness travel guide makes sure you experience all that New York City has to offer. Dynamic and diverse, New York City is bursting at the seams with unmissable sights, mouth-watering cuisines, and truly unique experiences. From the soaring skyscrapers of Manhattan to the trendy bars of Brooklyn, the vibrant jazz clubs of Harlem to the cobblestoned streets of SoHo, the city offers everything in abundance. Our annually updated guide brings New York City to life, transporting you there ... with expert-led insights and advice, detailed breakdowns of all the must-see sights, photographs on practically every page, and our trademark illustrations."--Publisher.